Cohyponormal operators with the single valued extension property - Ridgley Lange; Shengwang Wang (International Journal of Mathematics and Mathematical Sciences)
It is proved that in order to find a nontrivial hyperinvariant subspace for a cohyponormal operator it suffices to make the further assumption that the operator have the single-valued extension property.